1991
DOI: 10.1523/jneurosci.11-08-02477.1991
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the ventral origin of oligodendrocyte precursors in the rat spinal cord

Abstract: The neuroepithelial cells of the mammalian neural tube are thought to give rise to all classes of differentiated neurons and macroglial cells in the adult CNS. In most cases, the regulation and timing of commitment of neuroepithelial cells to specific differentiative pathways are unknown. It has been proposed that in developing spinal cord, the macroglial cells--astrocytes and oligodendrocytes--arise either by the direct transformation of radial glial cells in the developing cord or, alternatively, by the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
169
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(186 citation statements)
references
References 40 publications
15
169
2
Order By: Relevance
“…Therefore, the ordered appearance of these cells in vivo requires the OT to be intact. This seems to be fundamentally different from mammals, where oligodendrocytes arise in high-density (Williams et al, 1985;Warf et al, 1991) and clonal Temple and Raff, 1986) cultures with approximately the same timing as in vivo. Differentiation of OT cells here occurred without induction by extrinsic factors and therefore is more likely to be a removal of inhibitory influences that operate in the intact brain than a direct positive induction, although it is possible that removal of tissue from the intact brain triggered intrinsic induction to occur.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, the ordered appearance of these cells in vivo requires the OT to be intact. This seems to be fundamentally different from mammals, where oligodendrocytes arise in high-density (Williams et al, 1985;Warf et al, 1991) and clonal Temple and Raff, 1986) cultures with approximately the same timing as in vivo. Differentiation of OT cells here occurred without induction by extrinsic factors and therefore is more likely to be a removal of inhibitory influences that operate in the intact brain than a direct positive induction, although it is possible that removal of tissue from the intact brain triggered intrinsic induction to occur.…”
Section: Discussionmentioning
confidence: 74%
“…Spinal cord oligodendrocytes apparently arise only from ventral regions and then migrate dorsally to fill the remainder of the cord (Warf et al, 1991;Noll and Miller, 1993;Pringle and Richardson, 1993;Hall et al, 1996;Ono et al, 1997b;Miller et al, 1999;Sussman et al, 2000). In mammalian brain, oligodendrocytes have been reported to arise from the subventricular zone and migrate to both gray and white matter of the ipsilateral forebrain hemisphere (Levison and Goldman, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…7). In contrast, Warf et al (1991) demonstrated the ability of ventral but not dorsal spinal cord to give rise to oligodendrocytes in culture at E14.5. At later ages,both ventral and dorsal cord contain oligodendrocyte precursors, possibly due to migration of these from their ventral origin.…”
Section: Peripheral Gliamentioning
confidence: 86%
“…Furthermore, the in vitro isolation of glial-restricted precursors (GRPs) from the spinal cord (Rao and Mayer-Proschel, 1997;Rao et al, 1998), and their transplantation and differentiation into astrocytes and oligodendrocytes (Rao and Mayer-Proschel, 1997;Rao et al, 1998;Herrera et al, 2001), supports such a lineage model. However, the fact that GRPs can be isolated from dorsal as well as ventral embryonic spinal cords contrasts with studies demonstrating the ventral restriction of OLPs (Warf et al, 1991;Pringle and Richardson, 1993;Ono et al, 1995;Lu et al, 2002;Zhou and Anderson, 2002). This may be reconciled by the findings of Gabay et al (2003), who found that the deregulation of dorsoventral patterning in vitro, attributable in part to aberrant SHH production induced by fibroblast growth factor (FGF) signaling, may be responsible for the generation of oligodendrocytes by dorsally derived GRPs.…”
Section: Introductionmentioning
confidence: 96%